PENERAPAN SISTEM INFORMASI AKUNTANSI DAN AKUNTABILITAS DALAM PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (STUDI KASUS DI SMP NEGERI 4 KOTA MOJOKERTO) (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
UPT SMP NEGERI 4 is one of the educational units with a junior high school level which is addressed at Kel. Kranggan, Kec. Kranggan, Mojokerto City, East Java. In carrying out its activities, UPT SMP NEGERI 4 is under the auspices of the Ministry of Education and Culture. This study aims to analyze the extent to which accountability information systems are implemented in the management of school operational assistance funds at SMP Negeri 4 Mojokerto City. The method used is a qualitative method with a descriptive approach. Data collection techniques used are interviews and observation. The data analysis techniques used are: 1) data collection, 2) data reduction, 3) data display, 4) inference and verification. The results showed that the school's accounting information system and division of tasks had not been effective. Accountability for the management of BOS funds is good enough. Although some RKAS budgets have not been allocated properly. However, the procedure for reporting BOS funds complies with the Technical Instructions